Social Entrepreneurship Communication of Kampung Teknologi Foundation through the Digital Literation of MSMEs during COVID-19 Pandemic - Sulistiyawati Sulistiyawati; Nuriyati Samatan (Universitas Muhammadiyah Jakarta, 2021)
Information and Communication Technology (ICT) is significant for developing human resources in various villages in the current digital era. However, the implementation of ICT has experienced disruption due to the increasing spread of the COVID-19 virus, resulting in a decline in market mechanisms, especially in the Village MSME sector. Therefore, social innovation is needed by social entrepreneurs so that MSMEs can survive and compete with others, as has been done by the Kampung Teknologi Foundation (KTF) through digital literacy to MSMEs in villages. The method in this study used qualitative research using the Social Innovation Model. As a result, in social entrepreneurship communication, KTF carried out three essential stages, 1) Formalization: KTF used Law Number 6 of 2014 concerning Villages as a basis for empowering MSMEs. KTF initiated the empowerment of MSMEs in villages by introducing digital sales using social media, market places, e-commerce, and other digital applications; 2) Change processes: KTF implemented digital sales by initiating the Digital Up program, which is an entrepreneur empowerment program and was implemented after five-year KTF contributes to digital literacy; 3) Social Outcomes: In the application of digital literacy, only 30% of MSMEs have successfully switched to using digital technology. Therefore, good cooperation between one division and another is still needed, such as implementing new programs. It can minimize program failures, and implementing digital literacy can succeed and on target.